AL amyloidosis clonal plasma cells are regulated by microRNAs and dependent on anti‐apoptotic BCL2 family members. (24th January 2023) - Fishov, Hila; Muchtar, Eli; Salmon‐Divon, Mali; Dispenzieri, Angela; Zvida, Tal; Schneider, Claudio; Bender, Benjamin; Duek, Adrian; Leiba, Merav; Shpilberg, Ofer; Hershkovitz‐Rokah, Oshrat
Abstract: Background: Noncoding RNAs such as microRNAs (miRNAs) have attracted attention as biological pathway regulators, which differ from chromosomal translocations and gene point mutations. Their involvement in the molecular mechanisms underlying light chain (AL) amyloidosis pathogenesis is yet to be elucidated. Aims: To decipher specific miRNA expression profile in AL‐amyloidosis and to examine how miRNAs are involved in AL pathogenesis. Methods: The expression profile of miRNAs and mRNA from bone marrow (BM)‐derived CD138+ cells were determined using the NanoString nCounter assay and RNA‐Seq, respectively. The effect of aberrantly expressed miRNAs on potential molecular targets was analyzed by qRT‐PCR, Western blot, Mito‐potential assay, and Annexin‐PI staining. Results: Genes which were significantly differentially expressed between AL‐amyloidosis and MM, were found to be involved in cell growth and apoptotic mechanisms. Specifically, BCL2L1, MCL1, and BCL2 were upregulated in AL‐amyloidosis compared with MM and controls. The levels of miR‐181a‐5p and miR‐9‐5p, which regulate the above‐mentioned genes, were lower in BM samples from AL‐amyloidosis compared with controls, providing a mechanism for BCL2 family gene upregulation. When miR‐9‐5p and miR‐181a‐5p were overexpressed in ALMC1 cells, BCL2L1, MCL1, and BCL2 were downregulated and induced apoptosis. Treatment of ALMC‐1 cells with venetoclax, (BCL‐2 inhibitor), resulted in the upregulation of those miRNAs, the downregulation of BCL2, MCL1, and BCL2L1 mRNA and protein levels, and subsequent apoptosis. Conclusion: Our findings suggest that miR‐9‐5p and miR‐181a‐5p act as tumor‐suppressors whose downregulation induces anti‐apoptotic mechanisms underlying the pathogenesis of AL‐amyloidosis. The study highlights the post‐transcriptional regulation in AL‐amyloidosis and provides pathogenetic evidence for the potential use of BCL‐2 inhibitors in this disease. Abstract : BCL2 family members are highly expressed in AL amyloidosis compared with MM, underpinning the therapeutic potential of BCL2 inhibitors in this disease. miR‐9‐5p and miR‐181a‐5p act as tumor suppressors in AL amyloidosis by inducing apoptotic mechanisms.